Making a move in exercise referral: co-development of a physical activity referral scheme. (22nd December 2018) - Buckley, B J R; Thijssen, D H J; Murphy, R C; Graves, L E F; Whyte, G; Gillison, F B; Crone, D; Wilson, P M; Watson, P M
Abstract: Background: Translational research is required to ensure exercise referral schemes (ERSs) are evidence-based and reflect local needs. This article reports process data from the co-development phase of an ERS, providing an insight into (i) factors that must be considered when translating evidence to practice in an ERS setting, and (ii) challenges and facilitators of conducting participatory research involving multiple stakeholders. Methods: An ERS was iteratively co-developed by a multidisciplinary stakeholder group (commissioners, managers, practitioners, patients and academics) via five participatory meetings and an online survey. Audio data (e.g. group discussions) and visual data (e.g. whiteboard notes) were recorded and analysed using NVivo-10 electronic software. Results: Factors to consider when translating evidence to practice in an ERS setting included (i) current ERS culture; (ii) skills, safety and accountability; and (iii) resources and capacity. The co-development process was facilitated by needs-analysis, open questions, multidisciplinary debate and reflective practice. Challenges included contrasting views, irregular attendance and (mis)perceptions of evaluation. Conclusion: The multidisciplinary co-development process highlighted cultural and pragmatic issues related to exercise referral provision, resulting in an evidence-based intervention framework designed to be implemented within existing infrastructures. Further work is required to establish the feasibility and effectiveness of the co-developed intervention in practice.